2013
DOI: 10.4236/jgis.2013.56050
|View full text |Cite
|
Sign up to set email alerts
|

GIS-Based Local Spatial Statistical Model of Cholera Occurrence: Using Geographically Weighted Regression

Abstract: Global statistical techniques often assume homogeneity of relationships between dependent variable and predictors across space. This assumption has been criticized by statistical geographers as a fundamental weakness that may yield misleading result when it is applied to dataset with spatial context. To strengthen this weakness, a new method that accounts for heterogeneity in relationships across geographic space has been presented. This is one of the family of local spatial statistical techniques referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…which independent variable has the greatest influence in a particular region? (Nkeki and Osirike, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…which independent variable has the greatest influence in a particular region? (Nkeki and Osirike, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Where Y is the dependent variable (BLB prevalence), the betas β0 to βn represent the consequent number of the coefficients of predictors while 1 n X to X depicts the corresponding number of predictors and ε is error of residuals. Ordinary least square ANOVA contain different statistical tests which includes Joint F-statistics, Koenker statistics, Wald statistics and Jarque and Bera statistics which define the explanatory variables are significant to independent value or not (Nkeki and Osirike, 2013;Ahmad et al, 2021). Environmental factors that were used as explanatory variables were:…”
Section: Ols Model For Spatial Relationshipmentioning
confidence: 99%
“…Since the difference with respect to goodness-of-fit between the two models exceeded 4, it was concluded that GWR is the best approach (Lee and Choi, 2013 had lower levels of Sigma (σ) and residual squares than OLS. Koenker statistics (Nkeki and Osirike, 2013) had significant P-values, which implies that there was no fixed type of relationship between the dependent variables and the regional characteristics and that they varied by region. Figure 2 shows the distribution of regression coefficient and local R 2 for each region as estimated by GWR.…”
Section: Resultsmentioning
confidence: 99%
“…After performing the PCA analysis, a model of Geographically Weighted Regression (GWR) was used to explore the spatial relationship between communities directly affected by floods and localities with high and very high LoSoVI values. GWR is a local spatial statistical technique that assumes non-stationarity within relationships-i.e., that is the relationship between the dependent and the explanatory variables changes from location to location [49]. Thus the regression coefficient β k takes different values for each location.…”
Section: Methodsmentioning
confidence: 99%